Board specialty certifications for pharmacists in Arab countries: current needs and recommendations - Elnaem, Mohamed Hassan Abdelaziz; Jamshed, Shazia Qasim; Elkalmi, Ramadan Mohamed Mahmod (Archives of Global Professionals, 2017)
For more than three decades, the American Board of Pharmacy Specialties (BPS) has provided specialty-level certification programs for pharmacists – both nationally and internationally. This qualification certificate has been established to “Improve patient care through recognition and promotion of specialized training, knowledge, and skills in pharmacy practice and through board certification of pharmacists.”[1] Since its inception, about 25,227 pharmacists have been certified. Statistics showed that the vast majority of the certified pharmacists (n = 23,184, 92%) were from the USA, whereas the rest (n = 2043, 8%) were pharmacists from other countries. A list of the first seven countries in terms of the number of certified pharmacists is shown in [Table 1]. It is noticeable that three of these countries are Arab countries (ACs). The rest of countries have <100 of certified pharmacists.[2]